Galvanic Coupling of Copper and Carbon Steel in the Presence of Bentonite Clay and Chloride. Issue 5 (1st May 2022) - Braithwaite, Lindsay; Albrechtas, Katarina; Zagidulin, Dmitrij; Behazin, Mehran; Shoesmith, David; Noël, James J.
Abstract : The long-term containment plan for Canada's used nuclear fuel employs copper-coated carbon steel (CS) containers encased in compacted bentonite clay buffer boxes. In the hypothetical case of a through-coating defect, galvanic interactions between the Cu coating and the CS vessel are dependent on the conditions at the container surface. A zero-resistance ammeter was used to measure the galvanic current between Cu and CS electrodes at various area ratios in the presence of aerated 1 M NaCl and obstructive layers of bentonite slurry. The presence of bentonite resulted in an order of magnitude decrease in the corrosion rate of the steel. As shown by scanning electron microscopy (SEM) with energy dispersive X-ray (EDX) analysis and Raman spectroscopy, the extent of steel corrosion decreased significantly in the presence of bentonite slurry, favouring mild surface etching over oxide growth. Electrochemical impedance spectroscopy (EIS) measurements showed that the total impedance on carbon steel generally increased with bentonite layer thickness, but the total impedance on Cu plateaued when the layer exceeded 6 mm, consistent with trends in galvanic current density on carbon steel. The benign conditions produced by the bentonite slurry are attributed to the slightly alkaline pH and the hindrance of O2 diffusion.